A brief review on text summarization methods - Rautray, Rasmita; Swain, Lopamudra; Dash, Rasmita; Dash, Rajashree (International Journal of Engineering and Technology, 2018)
In present scenario, text summarization is a popular and active field of research in both the Information Retrieval (IR) and Natural Language Processing (NLP) communities. Summarization is important for IR since it is a means to identify useful information by condensing the document from large corpus of data in an efficient way. In this study, different aspects of text summarization methods with strength, limitation and gap within the methods are presented.Â Â Â